Characteristics of spontaneous nystagmus and its correlation to video head impulse test findings in vestibular neuritis - Zhang, Xueqing; Deng, Qiaomei; Liu, Yao; Li, Shanshan; Wen, Chao; Liu, Qiang; Huang, Xiaobang; Wang, Wei; Chen, Taisheng (Frontiers in Neuroscience, 2023)
Objective: To explore the direction and SPV (slow phase velocity) of the components of spontaneous nystagmus (SN) in patients with vestibular neuritis (VN) and the correlation between SN components and affected semicircular canals (SCCs). Additionally, we aimed to elucidate the role of directional features of peripheral SN in diagnosing acute vestibular syndrome. Materials and methods: A retrospective analysis was conducted on 38 patients diagnosed with VN in our hospital between 2022 and 2023. The direction and SPV of SN components recorded with three-dimensional videonystagmography (3D-VNG) and the video head impulse test (vHIT) gain of each SCC were analyzed as observational indicators. We examined the correlation between superior and inferior vestibular nerve damage and the direction and SPV of SN components, and vHIT gain values in VN patients. Results: The median illness duration of between symptom onset and moment of testing was 6 days among the 38 VN patients (17 right VN and 21 left VN). In total, 31 patients had superior vestibular neuritis (SVN), and 7 had total vestibular neuritis (TVN). Among the 38 VN patients, all had horizontal component with an SPV of (7.66±5.37) °/s, 25 (65.8%) had vertical upward component with a SPV of (2.64±1.63) °/s, and 26 (68.4%) had torsional component with a SPV of (4.40±3.12) °/s. The vHIT results in the 38 VN patients showed that the angular vestibulo-ocular reflex (aVOR) gain